Embryogenesis of formations of the sternoclavicular-mastoid region - Yakovets , R.V.; Proniaiev , D.V. (Морфологія / Morphologia / Morfologìâ, 2025)
Introduction. During the embryonic period of morphogenesis, the primary laying and rudimentary differentiation processes of the structures of the sternoclavicular-mastoid region occur: muscles, vessels and nerves. Violation of the processes of laying muscle elements leads to the occurrence of congenital defects, including: agenesis or abnormality in the attachment of the sternoclavicular-mastoid muscle, congenital torticollis, change in the number of abdomens. Purpose of the study: to establish the features of embryonic development and formation of components of the sternoclavicular-mastoid region during the embryonic period of human ontogenesis. Methods. The study was conducted on preparations of 30 embryos. Histological study of the sternoclavicular-mastoid region of human embryos was performed by making and studying under a microscope a series of consecutive sections. A series of histological sections 5-10 μm thick were made from paraffin blocks on a rotary microtome. Histological sections were performed in one of three mutually perpendicular planes (frontal, sagittal, horizontal), which made it possible to accurately determine the structure of different parts of the sternoclavicular-mastoid region. The preparations were stained with hematoxylin and eosin. Results. At the end of the 4th week of intrauterine development, vascular networks gradually form on the ventral surface of the rudiment of the rhomboid brain, which subsequently give rise to long neuronal arteries - the precursors of the main artery. Parallel to the first aortic arch, a trigeminal artery is formed, anastomoses with the previous ones. In the process of growth and differentiation of the structures of the neck, the trigeminal artery gradually integrates into the system of the internal carotid artery. At the beginning of the 5th week of intrauterine development, the division of the distal part of the internal carotid artery into cranial and caudal branches is noted. The cranial branch forms the olfactory artery, which supplies blood to the forebrain, in particular to the anterior artery of the choroid plexus, the anterior and middle cerebral arteries and the anterior communicating artery. The caudal branch forms the posterior communicating and posterior cerebral arteries, providing blood supply to the posterior structures of the brain. Our own studies of embryonic serial sections have shown that the topographic location of the ventral aortic sac and the third aortic arch correlates with the localization of the mesenchymal rudiments of the sternoclavicular-mastoid muscle. This suggests that early vascular structures play the role of anatomical landmarks for the growth of the accessory nerve and the formation of the future neurovascular bundle of the neck. Conclusions: 1. Study demonstrated that the development and differentiation of the structures of the sternoclavicular-mastoid region and the trapezius muscle occurs in parallel with the formation of the ventral aortic sac and the internal carotid artery, which primarily emphasizes the close relationship between the processes of development of the muscle elements of the sternoclavicular-mastoid region and angiogenesis. 2. The location of the first and third aortic arches has a close correlation and relationship with the localization of mesenchymal condensations of the sternoclavicular-mastoid muscle and the trapezius muscle, as well as with the formation of the fibers of the accessory nerve, which indicates the role of early rudiments of large vessels as anatomical landmarks for the formation of the neurovascular bundle of the neck. The internal carotid artery is formed by the interaction of the aortic sac, the third aortic arch, and the dorsal aorta. 3. Progressive elongation and increase in the volume of the sternocleidomastoid muscle and trapezius muscle correlates with the growth of the internal carotid artery and the formation of its branches, which indicates the integrative development of the structures of the neurovascular bundle of the neck.